Recognition of Multiple Hybrid Insulin Peptides by a Single Highly Diabetogenic T-Cell Receptor - Parras, Daniel; Solé, Patricia; Delong, Thomas; Santamaría, Pere; Serra, Pau (Frontiers in Immunology, 2021)
The mechanisms underlying the major histocompatibility complex class II (MHCII)-type 1 diabetes (T1D) association remain incompletely understood. We have previously shown that thymocytes expressing the highly diabetogenic, I-Ag7-restricted 4.1-T-cell receptor (TCR) are MHCII-promiscuous, and that, in MHCII-heterozygous mice, they sequentially undergo positive and negative selection/Treg deviation by recognizing pro- and anti-diabetogenic MHCII molecules on cortical thymic epithelial cells and medullary hematopoietic antigen-presenting cells, respectively. Here, we use a novel autoantigen discovery approach to define the antigenic specificity of this TCR in the context of I-Ag7. This was done by screening the ability of random epitope-GS linker-I-Ag7 beta chain fusion pools to form agonistic peptide-MHCII complexes on the surface of I-Ad alpha chain-transgenic artificial antigen-presenting cells (APCs). Pool deconvolution, I-Ag7-binding register-fixing, TCR contact residue mapping, and alanine scanning mutagenesis resulted in the identification of a 4.1-TCR recognition motif XL(G/A)XEXE(D/E)X that was shared by seven agonistic hybrid insulin peptides (HIPs) resulting from the fusion of several different chromogranin A and/or insulin C fragments, including post-translationally-modified variants. These data validate a novel, highly sensitive MHCII-restricted epitope discovery approach for orphan TCRs and suggest thymic selection of autoantigen-promiscuous TCRs as a mechanism for the murine T1D–I-Ag7-association.